2004
DOI: 10.1111/j.0105-1873.2004.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a detergent on skin response to methyldibromo glutaronitrile in sensitized individuals

Abstract: The present study was undertaken to evaluate the combined effect of the preservative methyldibromo glutaronitrile (MDBGN) and sodium lauryl sulfate (SLS) on the elicitation response of allergic contact dermatitis. 20 volunteers with contact allergy to MDBGN were patch tested with 5 concentrations (10, 50, 100, 500 and 1000 p.p.m.) of MDBGN alone and in combination with 0.25% SLS on the upper arms for 24 h. Skin reactions were evaluated by clinical scoring, and data were evaluated by logistic dose-response mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The risk of induction also depends on the number of exposures within a certain time frame (11). The combination of MDBGN and detergents such as those in liquid soaps has been shown to enhance skin reactions in sensitized individuals by a factor of 6.4 (12), which is in accordance with the concept of ‘danger’ signals produced by irritancy (13). Rinse‐off products, e.g.…”
Section: Discussionsupporting
confidence: 65%
“…The risk of induction also depends on the number of exposures within a certain time frame (11). The combination of MDBGN and detergents such as those in liquid soaps has been shown to enhance skin reactions in sensitized individuals by a factor of 6.4 (12), which is in accordance with the concept of ‘danger’ signals produced by irritancy (13). Rinse‐off products, e.g.…”
Section: Discussionsupporting
confidence: 65%
“…As stated before, an impaired skin barrier function will necessarily increase the risk of sensitization and elicitation of ACD. In line with this, combined exposure to irritants and sensitizers is known to significantly augment the response as assessed by measurement of TEWL and erythema .…”
Section: Bioengineering Parametersmentioning
confidence: 80%
“…Jensen et al (36) have shown, for instance, that 0.04% MDBGN once daily or 0.01% MDBGN four times daily had approximately equal capabilities of provoking allergic contact dermatitis. In contrast, a further aggravating influence on elicitation relating to the used product itself, namely concomitant exposure to potentially irritating detergents (37), was considered in this study, as the preparations used were based on commercial washing liquids. Zachariae et al described that the hand eczema ‘improved or cleared within 6 months' following identification of the contact allergen.…”
Section: Discussionmentioning
confidence: 99%